“Your behavior is not welcome here…”: forced internal displacement of sexual and gender minorities in Kenya - Emmy Kageha Igonya; Ebenezer Kwesi Armah-Ansah; Winstoun Muga; Kristefer Stojanovski (Frontiers in Sociology, 2025)
BackgroundWhile migration studies have boomed, little is mentioned about internal displacement of queer persons. In Kenya, internal displacement of sexual and gender minorities is often overlooked and not well understood, which results in increased marginalization and vulnerabilities. The article provides an in-depth analysis of forced serial internal displacement trajectories of sexual and gender minorities, and its effect on navigating socialites and livelihoods.MethodsWe draw on qualitative data conducted between 2010 and 2023 using participant observations, in-depth interviews, case histories, and focus group discussions with LGBTQ+ persons, as well as mothers and fathers of gay men in Kenya. We used a thematic approach and principles of interpretive anthropology to organize and describe the meaning of the data as a continuous process. Broader themes were identified from the beginning of the first study, resulting in the development of a codebook framework that was reiterated over time.FindingsOur findings show that sexual and gender minorities are forced into internal migration. Factors informing are located at the individual, interpersonal, institutional, and communal levels. We identified three main themes with eight subthemes. The main themes were (1) reasons for migration, which were often related to stigma, violence and oppression, (2) patterns of migration, which primarily had rural to urban patterns and instability, and (3) kinship, networks, and social systems, which required rebuilding, and gaining “respectability” from kin.ConclusionThere can be little doubt that sexual and gender minorities face stigma and discrimination across levels of the socioecological model, and that in most cases, there has been multiplied grievances and anti- LGBTQ+ activities instigating serial forced migration. Forced serial displacement of sexual and gender minorities in Kenya requires research attention, and it might be better served if examined through the lens of “forced migration,” given the non-voluntary aspects of fleeing and displacement. Rethinking LGBTQ+ IDPs through the lens of coercion may better capture the lived experiences given the structural stigma and violence in which they live and cannot escape.